Experimental Study of Iraqi Light Naphtha Isomerization over Ni-Pt/H-Mordenite - M. Hussain, Halah; A.K. Mohammed, Abdulhaleem (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Hydroisomerization of Iraqi light naphtha was studied on prepared Ni-Pt/H-mordenite catalyst at a temperature range of 220-300°C, hydrogen to hydrocarbon molar ratio of 3.7, liquid hourly space velocity (LHSV) 1 hr-1 and at atmospheric pressure. The result shows that the hydrisomerization of light naphtha increases with the increase in reaction temperature at constant LHSV. However, above 270 0C the isomers formation decreases and the reaction is shifted towards the hydrocracking reaction, a higher octane number of naphtha was formed at 270 °C.